Light-induced nuclear export reveals rapid dynamics of epigenetic modifications - Yumerefendi, Hayretin (Nat Chem Biol, 2016)
We engineered a photoactivatable system for rapidly and reversibly exporting proteins from the nucleus by embedding a nuclear export signal in the LOV2 domain from phototropin 1. Fusing the chromatin modifier Bre1 to the photoswitch, we achieved light-dependent control of histone H2B monoubiquitylation in yeast, revealing fast turnover of the ubiquitin mark. Moreover, this inducible system allowed us to dynamically monitor the status of epigenetic modifications dependent on H2B ubiquitylation.